Family Medicine Approach to a 21-Month-Old Child with Tuberculosis and Stunting - Letius, Fairuz Zefiro; Atzmardina, Zita (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
Approximately 205,000 children die annually from tuberculosis (TB), 90% of these deaths occurring in undiagnosed and untreated cases. This disease also weakens nutrition, and conversely, poor nutrition increases the risk of developing TB. The prevalence of malnutrition in children with TB ranges from 7.1% in resource-rich South Africa to 75.2% in Pakistan. Childhood stunting has profound long-term consequences, including physical growth and impaired cognitive development. The visit was conducted in July–August 2025 as part of a comprehensive family medicine management program within the Cikupa Community Health Center (Puskesmas) area. We provided patient-centered interventions with a family and community approach. Within the following month, we observed improvement in the patient's symptoms, a return to normal leukocyte levels, and increased appetite, height, and weight after implementing a comprehensive and holistic treatment plan. This case demonstrates that holistic and comprehensive management using a family medicine approach addresses not only the medical diagnosis but also related family and community factors.